Potential of Anti-Secretory and Cytoprotective Effect from Azadiradione as GERD Prevention - Corinna Faustina; Villicia Angellika; Alya Rahmadani; Rosalie Dorothea; Ricky Fajar Adiputra; Ziske Maritska (Fakultas Kedokteran Universitas Sriwijaya, 2022)
Gastroesophageal Reflux Disease (GERD) is a pathological state due to stomach reflux within the esophagus, which causes necrosis of esophageal mucosa, resulting in erosions, ulcers, and other complications. GERD is still a growing global issue with 783.95 million cases worldwide in 2019. Although PPIs were used as medications to treat GERD, there were refractions and adverse effects to the patients. Azadiradione, terpenoids that can be found in A. indica and various plants, has potential as alternative H+/K+ ATPase inhibitor sources with its anti-secretory and cytoprotective activity. Some studies explain that there is also adverse effects of azadiradione. Further research are needed to determine alternative sources, safety dosage, usage duration, side effects, also drug-food or drug-drug interaction of azadiradione.